PENGEMBANGAN VIDEO ANIMASI SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI GETARAN HARMONIS DI SMA - Rizki Khodijah Matondang; Zulhelmi Zulhelmi; Azizahwati Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Animated video as a learning media is a learning media that packs animated videos into powerpoint media. In addition to animated videos, on powerpoint media there are also learning tools to support learning media. Animated video as a learning media in this study was developed on the material of Harmonic Vibration in SMA. The purpose of this research is to produce animated videos as a valid learning media and can be used for teaching and learning physics in SMA on Harmonic Vibration material. This research is expected to make it easier for students to understand the concept of harmonic vibrations. In addition, this media is expected to make it easier for teachers to convey the lessons taught to students, especially in understanding the concept of Harmonic Vibration in SMA. This type of research is Research and Development (R&D) using the ADDIE development model. This research is only limited to the development stage. The research instrument used in this study was the media validation assessment sheet and the materials used by the validator to assess the feasibility of using animated videos as learning media for teaching and learning activities. Data analysis in this study used quantitative data analysis, by calculating the average validity score of each validity indicator. The results showed that the animated video as a learning media was declared valid with an overall average score of 3.35 with a very good category, so it was declared feasible to be used in teaching and learning physics on harmonic vibration material in SMA.Key Words : Animated Video, Learning Media, Harmonious Vibration